Childhood Digital Exposure to Sexual Content: Through the Lens of Developmental Psychopathology - Lakshmi Sravanti; Arul Jayendra Pradeep Velusamy; Kiragasur Madegowda Rajendra; John Vijay Sagar Kommu (Journal of Psychosexual Health)
Despite the numerous advantages offered by the digital medium, one notable drawback has been the early exposure to sexual content. In contemporary society, the omnipresence of the Internet, coupled with the pervasive influence of social media platforms, exposes children to sexual content, conversations, and vernacular at increasingly younger ages. Such content, ranging from mild-to-graphic representations, poses cultural, legal, and ethical considerations. Previous studies reveal that a significant proportion of adolescent Internet users encounter pornographic material before the age of 18. In this situation, it is very important to understand the factors that influence exposure, with parental oversight and peer-mediated exposure shaping adolescents’ responses. This review examines sociocultural factors contributing to childhood exposure to sexual content using a life-course perspective, its impact on development, and implications for intervention. Through this exploration, we elucidate the intricate interplay between technological advancements, social dynamics, and individual vulnerabilities, offering insights for clinicians, policymakers, and educators alike.